(3eHGOF GdEbJUGO GdSjGSj (B/s - (3RjfH, MSjf YhV Gddgs; (3YOdj fGTO, ShRjs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2007)
(3jVe ebOeI dYde GdGbJUGO(B: (3GdeTcdI GdGbJUGOjI, efgL Yde GdGbJUGO, GdePGgH hGdfXe GdGbJUGOjI(B: (3GdePGgH GdGbJUGOjI, GdfXe GdGbJUGOjI, GdShb hfXQjI GdKef(B: (3GdSb, GdWdH, GdYQV, Kef GdJhGRf, fXQjI GdGfJGL(B: (3eaghe acQI GdGfJGL, OGdI GdGfJGL, fXQjI GdJhRjY(B: (3GdbhGYO GdYGeI GdJj JMce CKeGf YfGUQ GdGfJGL, CKeGf NOeGJ YfGUQ GdGfJGLs
Keywords: (3GdGbJUGO GdSjGSjs; (3GdGfJGLs; (3GdfXe GdGbJUGOjIs